Forensic Linguistics Study on Natalius Pigai'S Speech for Central Javanese Ethnic (Jokowi and Ganjar Pranowo as an Object) - Machdori; Tadjuddin Maknun; Ery Iswary (Hasanuddin University, 2023)
There are many cases of spreading information containing hate speech in Indonesia. Hate speech can mean acts of communication carried out by an individual or group in the form of provocation, incitement or insult to another individual or group. Hate speech usually concerns aspects of race, skin color, gender, disability, sexual orientation, nationality, religion and others. This research specifically examines the ethnicity of Central Java, Indonesia. This article review aims to 1) describe elements of contempt for ethnic Central Java, namely Joko Widodo and Ganjar Pranowo, and 2) describe whether the statement forward by Natalis Pigai is identified as hate speech that violates the ITE Law of Indonesia Article 45A. The method of data collection is done by reviewing the news that has existed so far. This research review uses a qualitative descriptive analysis. The results of this study found five indications of forms of racism utterances made by Natalius Pigai namely racism, provocative, hateful, insulting and lying. This action violates the applicable ITE Law in Indonesia.